IMPACT OF WIND LOADS ON LONG-TERM FUEL CONSUMPTION AND EMISSIONS IN TRANS-OCEANIC SHIPPING - Vettor, Roberto; Prpić-Oršić, Jasna; Guedes Soares, Carlos (Brodogradnja, 2018)
The influence of weather conditions on fuel consumption and CO2 emissions for a containership is assessed by calculating the total added resistance, for various sea-states and relative wave directions, through a time domain procedure. The present article extended a formerly published research presented during the IMAM2015 conference [1] providing a deeper insight of the methodology adopted furtherly discussing the results achieved. In particular, the present paper studies the impact of wind velocity and directionality on the ship speed and its relative importance when compared with the wave added resistance. Moreover, considering the most commonly sailed routes in the North Atlantic, the long-term rate of increment of fuel consumption and CO2 emissions is estimated comparing the resulting ship performance with the wave climate expected for these specific routes.